Dialectical hermeneutics of narratives: a proposal for the analysis of biographies - Gonçalves Brandão Rodrigues, Emanuelle (2022)
This article presents a methodology for the analysis of biographical narratives based on Ricoeurian hermeneutics. From the Dialectical Hermeneutics of Narratives, it seeks to demonstrate how literature and philosophy can be constituted as important interfaces for research in communication. The results point to the need to broaden the theoretical horizon of the field of Communication and the constitution of its objects, which the studies of religion in the area have sought to contribute.